Feasibility comparison of HAC algorithm on usability performance and self-reported metric features for MAR learning - Cheng L.K.; Selamat A.; Zabil M.H.M.; Selamat M.H.; Alias R.A.; Puteh F.; Mohamed F.; Krejcar O.; Herrera-Viedma E.; Fujita H. (IOS Press, 2023)
Augmented reality; Cluster analysis; Learning systems; Usability engineering; Agglomerative clustering; English language teaching; Mobile augmented reality; Unsupervised machine learning; Usability; Clustering algorithms